Penerapan Pembelajaran Kooperatif Model Student Teams Achievement Division (STAD) Untuk Meningkatkan Nilai Akademik Matematika Kelas 7A SMP Kristen Immanuel II Kubu Raya - Hendra Wijaya (Ilmiah Manajemen Bisnis, 2019)
Abstract — The objective of this research is to increase mathematics academic scores by using Student Teams Achievement Division (STAD). The research design used in this study was action research. The subject of the study was the students of class 7A of SMP Kristen Immanuel II Kubu Raya as many as 42 students. The researcher conducted two cycles of action in which the frst cycle consisted of nine meetings and the second cycle consisted of 16 meetings. The tools for collecting the data were observation, exercises, interview, quiz, test, feld notes and documentation. Stages were used in the form of classroom presentations, group work, test, score improvement of individual and group awards. The researcher found that during the action research, the students have shown their improvement. Compared to the frst pre-test, the students’ mean score increased as many as 6,68% at the end of the frst cycle and as many as 11,86% at the end of the second cycle. While compared to the frst cycle, it increased 4,76%. Compared to the preliminary data the percentage of the number of students who passed the minimum passing grade was also increased as many as 5,55% on the frst cycle and as many as 13,81% on the second cycle. While compared to the frst cycle, it increased 7,82%. From the students questionnaire and interview, the researcher found that during the action, the students have shown that they became more joyful in learning Math with STAD as the percentage of positive responses was 68% from the questionnaire and 87% from the interview. Keywords — math, student teams achievement division,students achievement